2011
DOI: 10.1098/rstb.2010.0251
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of blast lung injury during recent military conflicts: a retrospective database review of cases presenting to deployed military hospitals, 2003–2009

Abstract: Blast injuries are becoming increasingly common in military conflicts as the nature of combat changes from conventional to asymmetrical warfare and counter-insurgency. This article describes a retrospective database review of cases from the UK joint theatre trauma registry from 2003 to 2009, containing details of over 3000 patients, mainly injured in Iraq and Afghanistan. During this period, 1678 patients were injured by explosion of whom 113 had evidence of blast lung injury. Of the 50 patients who survived t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 10 publications
0
44
1
3
Order By: Relevance
“…While this is a very 'safe' definition of blast lung where it is essential to exclude all other possibilities, it will exclude blast lung injuries when it co-exists with other injury types, which is common with conventional munitions and terrorist bombs and hence may underestimate the occurrence of blast lung in current in military casualties. Perhaps the most recent assessment of the incidence is given by Smith et al [13], where the incidence was found to be approximately 11 per cent in casualties who also suffered other (particularly penetrating) injuries.…”
Section: Classification Of Blast Injuriesmentioning
confidence: 99%
“…While this is a very 'safe' definition of blast lung where it is essential to exclude all other possibilities, it will exclude blast lung injuries when it co-exists with other injury types, which is common with conventional munitions and terrorist bombs and hence may underestimate the occurrence of blast lung in current in military casualties. Perhaps the most recent assessment of the incidence is given by Smith et al [13], where the incidence was found to be approximately 11 per cent in casualties who also suffered other (particularly penetrating) injuries.…”
Section: Classification Of Blast Injuriesmentioning
confidence: 99%
“…The lungs showed the most severe damage after the blast injury [1,27,28]. In the burn-blast combined injury group, the lungs were also severely damaged.…”
Section: Discussionmentioning
confidence: 93%
“…With the development of high-technology weaponry, the morbidity of combined injuries sustained in local wars and terrorist attacks has increased rapidly [1,2]. The detonation of an explosive generates shock wave and heat, causing burn-blast combined injury and aggravating the wound by the interaction of blast and burns [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…14 The default entry criterion for UK JTTR is a casualty who triggers trauma team activation in a deployed field hospital or Primary Casualty Receiving Facility afloat. The entry criteria were expanded in 2007 to include all trauma patients returned to Royal Centre for Defence Medicine for definitive treatment, irrespective of whether a trauma team response was mandated.…”
Section: Methodsmentioning
confidence: 99%
“…Anonymised data were supplied from the JTTR database, and according to institutional agreement ethical approval was not required. 14 Only patients with complete recordings of their physiological parameters on arrival at hospital were included in the study (SBP, HR, GCS, RR). Due to the nature of the JTTR and its inclusion criteria, patients in the study were assumed to be non-ambulant.…”
Section: Methodsmentioning
confidence: 99%